1999
DOI: 10.1007/pl00005354
|View full text |Cite
|
Sign up to set email alerts
|

Mesolimbic NMDA receptors are implicated in the expression of conditioned morphine reward

Abstract: Systemic administration of a variety of N-methyl-D-aspartate (NMDA) receptor antagonists inhibits morphine's rewarding properties in the conditioned place preference test. In this study, we investigated the anatomical loci implicated in the inhibition of expression of morphine's reward by bilateral microinjections of a selective NMDA antagonist into the mesolimbic areas, including ventral tegmental area and nucleus accumbens. During conditioning, injections of 1 mg/kg morphine were associated with placing rats… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
37
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 47 publications
8
37
0
Order By: Relevance
“…Thus, despite the lack of a direct ethanol effect on FOS expression in the VTA of DBA/2J mice (Hitzemann and Hitzemann, 1997), our finding of conditioned FOS increases in this brain area appears consistent with many other findings implicating this area in the mediation of ethanol's primary reinforcing effects. Involvement of the VTA in ethanol-induced conditioning is also consistent with findings from several studies suggesting that this brain area plays an important role in place preference conditioning induced by other abused drugs (Gholami et al, 2003;Harris and Aston-Jones, 2003;Neumaier et al, 2002;Popik and Kolasiewicz, 1999). In all of these studies, effects on CPP were believed to be due to modulation of VTA dopamine cells.…”
Section: Conditioned Changes In Fossupporting
confidence: 89%
“…Thus, despite the lack of a direct ethanol effect on FOS expression in the VTA of DBA/2J mice (Hitzemann and Hitzemann, 1997), our finding of conditioned FOS increases in this brain area appears consistent with many other findings implicating this area in the mediation of ethanol's primary reinforcing effects. Involvement of the VTA in ethanol-induced conditioning is also consistent with findings from several studies suggesting that this brain area plays an important role in place preference conditioning induced by other abused drugs (Gholami et al, 2003;Harris and Aston-Jones, 2003;Neumaier et al, 2002;Popik and Kolasiewicz, 1999). In all of these studies, effects on CPP were believed to be due to modulation of VTA dopamine cells.…”
Section: Conditioned Changes In Fossupporting
confidence: 89%
“…Therefore, one could expect that the inhibition of NMDA receptors might produce a reverse effect. Consistent with this idea, we have previously shown that administration of the NMDA receptor antagonist into VTA inhibits the expression of place preference conditioned with morphine (Popik and Kolasiewicz, 1999).…”
Section: Discussionsupporting
confidence: 61%
“…These data are largely consistent with those of previous studies, which, however, have been confined to morphine and cocaine. Thus, both the acquisition and the expression of morphine place conditioning was blocked by glycine antagonists (MRZ 2/570 and L-701,324) and by an uncompetitive NMDA antagonist (Popik et al 1998); in a later study, a competitive NMDA antagonist was shown to block the expression of morphine place preference when administered systemically or directly within the nucleus accumbens or ventral tegmental area (Popik and Kolasiewicz 1999). In contrast, the uncompetitive NMDA antagonist dizocilpine blocked the acquisition but not the expression of cocaine place preference (Cervo and Samanin 1995), and the same results have been reported previously for ACPC (Kotlinska and Biala 2000).…”
Section: Effects Of Acpc On the Expression Of Drugconditioned Place Pmentioning
confidence: 93%
“…Within this region, there are extensive bi-directional interactions between DA inputs from the ventral tegmental area and glutamatergic inputs from forebrain sites, such as hippocampus and amygdala, that are known to be involved in place conditioning (Everitt et al 1991;Tzschentke 1998). These DA-NMDA receptor interactions within the accumbens shell are a likely candidate for a site at which both DA and NMDA receptor antagonists block the acquisition of drug-conditioned place preferences (Tzschentke andSchmidt 1995, 1997;Popik and Kolasiewicz 1999). However, in addition to direct DA-NMDA interactions, DA and glutamate synapses are co-localized on the dendritic spines of medium spiny neurons in the nucleus accumbens (Gerfen 2000;Onn et al 2000).…”
Section: Mechanisms Of Acpc Effects On the Acquisition Of Drug-conditmentioning
confidence: 99%